Crossfire trail - L'Amour, Louis, 1908-1988 (Bantam Books, 2009)
Rafe Caradec promises a dying man that he will save the Long Valley ranch in Wyoming for the man's wife and daughter. But the daughter does not trust him and plays into the greedy hands of enemy ranchers.